2016
DOI: 10.1002/ajpa.23043
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal maxillary ontogeny in extant humans and the utility of prenatal maxillary morphology in predicting ancestral affiliation

Abstract: Objectives The midface of extant H. sapiens is known to undergo shape changes through fetal and neo-natal ontogeny; however, little work has been done to quantify these shape changes. Further, while midfacial traits which vary in frequency between populations of extant humans are presumed to develop prenatally, patterns of population-specific variation maxillary shape across ontogeny are not well documented. Only one study of fetal ontogeny which included specific discussion of the midface has taken a 3D geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Freidline, Gunz, and Hublin (2015) compared the ontogenetic and static allometry (i.e., the covariation between shape and size) of several geographically diverse human populations using geometric morphometric techniques. Their results support previous studies by showing that population differences in facial morphology are already present early in ontogeny, possibly prenatally (e.g., Bastir & Rosas, 2004;Lieberman, McBratney, & Krovitz, 2002;Mooney & Siegel, 1986;Nicholas, 2016;Ponce de Leon & Zollikofer, 2001). They also demonstrated subtle differences between populations in the patterns of absolute and relative growth and development.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Freidline, Gunz, and Hublin (2015) compared the ontogenetic and static allometry (i.e., the covariation between shape and size) of several geographically diverse human populations using geometric morphometric techniques. Their results support previous studies by showing that population differences in facial morphology are already present early in ontogeny, possibly prenatally (e.g., Bastir & Rosas, 2004;Lieberman, McBratney, & Krovitz, 2002;Mooney & Siegel, 1986;Nicholas, 2016;Ponce de Leon & Zollikofer, 2001). They also demonstrated subtle differences between populations in the patterns of absolute and relative growth and development.…”
Section: Introductionsupporting
confidence: 90%
“…Previous studies have already shown that population differences in facial morphology develop early, possibly prenatally (Bastir, O'Higgins, & Rosas, 2007; Bulygina et al, 2006; Freidline et al, 2015; Sardi & Ramirez‐Rozzi, 2012; Vidarsdóttir et al, 2002; Viðarsdottir & O'Higgins, 2003); however, the morphological variation in prenatal stages has only been investigated in few studies (Mooney & Siegel, 1986; Weinberg, 2005; Morimoto, Ogihara, Katayama, & Shiota, 2008; Nicholas, 2016). Using geometric morphometric techniques, Nicholas (2016) found shape differences in the fetal maxilla between African‐ and European‐Americans as early as the second trimester. The results of our morphological analysis further support these findings, as shape differences between the three populations can be observed already around birth (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…), a comparison of specimens from populations with different ancestries will help clarify this question. Nicholas () found morphological differences between European‐Americans and African‐Americans in the maxilla already present before birth; whether this translates into different bone modeling patterns is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies (Enlow, ; Rosas and Bastir, ) indicate sex‐based differences in external crania starting at puberty, whereby male growth rates increase and female's slow, it could very well be that the slight sex‐based differences found in the current study would be accentuated in an older sample. However, it is important to note that sex‐based differences in external facial ontogeny depend on the specific traits analyzed, and they can appear at different times depending on population affinity (see Bulygina et al, ; Nicholas, ). It is likely that ontogenetic processes related to sexual dimorphism among internal facial structures are equally complicated and need further study among larger, diverse samples.…”
Section: Discussionmentioning
confidence: 99%